Phytomining Potential of Jatropha curcas and Sansevieria trifasciata for Chromium (Cr) and Vanadium (V) Uptake from Red Mud Amended with Sludge-Manure Mixture - Adjie Praja Ardin; Voijant Tangahu Bieby; Yulikasari Andriyan; Arliyani Isni; Mashudi; Titah Harmin Sulistyaning; Ramadhani Muhammad Alif; Fauziah Natasya Febriani; Lam Yeng Ming; Wang Yamin; In Hurun; Soesilo Mery Maryanawati (BIO Web of Conferences)
The rapid growth of the alumina industry has significantly increased red mud production, with each ton of alumina yielding 0.8 to 1.5 tons of this byproduct. Red mud is a highly alkaline residue produced during bauxite refining, containing various metals including chromium (Cr) and vanadium (V), which pose significant environmental risks if not properly treated. Effective management and valorization of red mud are essential to mitigate environmental contamination and exploit its economic potential. Phytomining, a bioremediation strategy utilizing hyperaccumulator plants, offers a promising method for extracting economically valuable metals from red mud. This study investigates the phytomining capacity of Jatropha curcas and Sansevieria trifasciata to uptake Cr and V from red mud amended with a 5% sludge-manure mixture. The experiment was conducted over a 28-day period, during which both species were cultivated in red mud media with the amendment. The phytomining capacity of the plants was determined by measuring the metal accumulation, analyzed on days 0, 14, and 28 using acid digestion and ICP-OES analysis. Results showed that both plant species preferentially accumulated metals in their root systems rather than in their aerial parts. Jatropha curcas absorbed 1.6 mg/kg of Cr and 2.9 mg/kg of V, while Sansevieria trifasciata exhibited higher uptake, with 2.5 mg/kg of Cr and 4 mg/kg of V. These findings highlight the phytomining potential of these species in recovering valuable metals from red mud.